Hyperuricemia and hypertension in primary health care center in Kulon Progo - Nor Anita Ulfah; Hari Kusnanto; Cornelia Wahyu Danawati (Berita Kedokteran Masyarakat (BKM), 2016)
Hyperuricemia and hypertension in Wates primary health care centerPurposeThe purpose of this paper was to determine the relationship between hyperuricemia and hypertension occurrence in Wates primary health care center.MethodA cross-sectional study was conducted using medical records of 220 patients with the age of 18 years or older who met the inclusion criteria in Wates primary health care center in 2015.ResultsThe study found that hyperuricemia was associated with hypertension occurrence in Wates primary health care center in 2015, while age and dyslipidemia were confounders in the hyperuricemia and hypertension relationship. ConclusionIt was found that hyperuricemia had some influence on hypertension occurrence. There are many etiological factors associated with hypertension causing the difficulty of predicting the most common causes of hypertension. A cohort study should be done for further study. Early detection of elevated serum uric acid levels as a risk factor for hypertension needs to be done, in order to prevent hypertension.